Bringing in the Librarians: Rethinking Collaboration for Political Science Research Projects. Issue 1 (2nd January 2016) - Haigh, Adam E.; Kinsella, Chad J.
ABSTRACT: Librarians play a key role in undergraduate research yet there is infrequent collaboration using this key group of stakeholders in assigning and researching term papers. This case study reviews the impact of faculty and librarian collaboration in assigning and completing research projects in two upper level political science courses. Library instruction was primarily delivered—once at the beginning and then again in the middle of the semester. The research demonstrates how with active learning techniques, audience polling, and encouraging class participation from the students, our goal was to improve the quality of sources and help the students become better independent researchers.